Effect of Youth Unemployment on the Rate of Crime in Nigeria: A Study of DSTV Viewing Centers in Two Local Government Areas in Nigeria - Kazeem, Lamidi; Egbewole, Isiaka Kalwole (Annals of Spiru Haret University. Economic Series, 2021)
This study examined the effect of youth unemployment on crime rate among youth unemployment (spectators)in selected DSTV viewing centers in two local government areas in Nigeria. The study was guided by two specific objectives on youth unemployment and crime rate. The research design is descriptive survey and the research instrument is a structured questionnaire. Two hundred and thirty two (232) questionnaires were distributed in all but only One hundred and ninety four (194) that is (83.62%) were retrieved in usable forms. Data collected through questionnaire was analyzed with an inferential statistical tool of multiple regression analysis. The findings showed R squared is 0.034 which indicated that youth unemployment contributed 2.4% of the total variation to the demographic variable of the respondents. With F (5,188) = 1.304, p>.05b, with an R2 of .034, it is therefore concluded that there is no relationship between demographics variables and youth unemployment.The research found out that youth unemployment has significant but marginal effect on crime proneness. Variables were formulated and tested on the relationship between youth unemployment and psychoactive substance use which indicated they both have a negative effect.Therefore, it can be safely concluded that there is no statistically significant relationship between youth unemployment and psychoactive substance use. Also, the findings revealed that there is no significant relationship between demographics variables ofage, marital status, academics qualification, nature of work and source of income and youth unemployment.It is therefore recommended that government must undertake an effective reappraisal of her various public policies and programmes designed to generate adequate economic opportunities capable of creating jobs for the unemployed youths.